INDIA’S NATIONAL SOLAR PROGRAM: NATIONAL OBJECTIVES VERSUS INTERNATIONAL COMMITMENTS - Gautam, Dr Savita; Khattar, Dr. Komal J; Bhattacharya, Kriti Gautam (The journal of contemporary issues in business and government, 2022)
The Central and State Government of India are giving a lot of focus on promoting solar power for the growing energy needs of India. To pursue the aim theNational Solar Mission named as JawaharLal Nehru Solar Mission was started in 2010. The Solar Mission projected that by 2022, It should provide 100 GW solar capacity. India aimed to be among the top five solar markets in the world.lt is expected that India will become the third largest solar market across the globe in 2017. With the increasing growth of industry and population, There would be a paradigm shift in the energy needs, the government in India had always beenencouraging use of renewable sources off energy. Indian government expects that by the end of this decade 40% off the energy needs would be fulfilled by renewable sources. This growth in sustainableenergy needswould be supported by major improvements in the role played by renewable sources, this would also help in completing the international commitments meet at Paris agreement.5With the kind of policy changes made by the government, it is expected that by 2030 there should be a major reduction and in greenhouse gas emissions, which maybe 35%below 2005, whereas original commitments stand at 20 to 25 percent.